Employing cleaner production strategies to achieve competitive advantage (Applied study in the State Company for the manufacture of cars and equipment - battery factory - Babylon factory) - Emad Hashem Mohammed; Alaa Mohammed Obaid (Journal of Madenat Alelem University College, 2022)
The significant increase in production after technological wealth and the use of high automation resulted in an increase in the volume of pollution, waste and excessive consumption of materials and energy, which led to a rise in the costs of resources and energy, and consequently its impact on the competitive position of local economic units that still operate with traditional systems and technologies, although companies (External) competition The use of modern systems and technologies, which improved the quality of their products, reduced their costs, and met the environmental requirements, which made it necessary for local economic units to take the same approach in applying modern systems and technologies competitive advantage. The current research aims to employ the four cleaner production strategies (Reduce, Reuse, Remanufacture, Recycle) to reach an environmentally friendly product at low costs, which enhances the competitive advantage. The research concluded that employing cleaner production strategies reduces pollution and waste, achieves a safe and sound work environment, reduces costs and enhances competitive advantage.